Basic Design Education Approach Example and Comparative Analysis - Elif Özgen; Mine Tunçok Sarıberberoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The architectural education process in most state and foundation universities in our country is generally based on the backbone of 'Basic Design Education'. The study is based on the course outputs of Bolu Abant İzzet Baysal University in the Fall Semester of the 2023-2024 academic year. Within the scope of the course, although a similar course operation was determined for two different branches, different activities were deliberately carried out, especially in the concept development process. With this approach, the students of one branch were given a large number of assignments and applications to experience the design process through various experiments with different disciplines. In the other branch, the scope was broader and the emphasis was on examples, assignments, and applications within architecture. The methodology outlined in this study is qualitative in approach and deals with a comparative analysis of the approaches between the branches. The study aims to contribute to the improvement of the learning-oriented model in the process of Basic Design Education in Architecture undergraduate education, as well as to create a discussion environment on the linear or inverse proportions of the educational approach that requires more effort, time and labor in quantitative terms on the results.